Automated programming of cooperating industrial robots - Wagner, Maximilian; Reitelshöfer, Sebastian; Heß, Peter (ISR/Robotik 2014; 41st International Symposium on Robotics, 2014)
Due to the technological development, products are becoming increasingly complex. In order to implement their sophisticated manufacturing processes, more and more often cooperative industrial robots are used. The challenge in cooperative applications is the complicated programming. Using an automated programming that is done by a generator is a corrective for this. The aim of the project described here is to divide application processes on two industrial robots by one robot holding the tool and the other one the workpiece. The adhesive or sealant application serves as an example for this. The process movements are effectively divided between the two robots in consideration of boundary conditions. To enable programming of such complex tasks for non-experts, an automated program generation with an intuitive programming interface is used.